Planning and executing a global health experience for undergraduate nursing students: A comprehensive guide to creating global citizens. (May 2016) - Visovsky, Constance; McGhee, Stephen; Jordan, Elizabeth; Dominic, Sara; Morrison-Beedy, Dianne
Summary: The preparation of future baccalaureate-prepared nurses will require undergraduate students to have both cultural awareness and global or international health competencies in order to meet the increasingly complex health care needs of a diverse community. Additionally, the nursing accrediting bodies have identified global healthcare as an area of core knowledge for clinical nurses. In order to meet the workforce needs, and provide global education of the undergraduate student body, we designed an international clinical experience within the undergraduate Community/Population Health course. The purpose of this article is to provide a guide for faculty in the planning, infrastructure needs, and implementation of a global clinical experience for undergraduate nursing students, in the context of the United States with addressing university concerns for student safety and security while abroad. Highlights: Global clinical experiences prepare future nurses for diverse patients. Advance planning is crucial for successful global student experiences. Infrastructure supports to implement a successful global program are necessary. Policies and risk assessments for travel ensure safety of students and faculty.